ΜΕΤΡΟΝ, ΜΕΤΡΙΟΝ, ΜΕΤΡΙΟΤΗΣ. Early Greek Concepts of Measure - Aleksandra Mathiesen (Ethics in Progress, 2014)
Submitted article presents a variety of the concept of measure in the early Greek investigations of nature, development of ethical and political structures, fundamental norms of the arts and crafts, and conclusively, searches for understanding of the ἄνθρωπος μέτρον challenge. Among the crucial notions of the early Greek investigations, measure was one of the most receptive: from speculative inquiries to ethical considerations, from theoretical constructions to methodological directives, from normative arrangements to technical solutions. The thinkers and sages introduced the concept of measure into the normative reflection of the ethics and politics, enclosing the most essential and fundamental prescriptions for noble, virtuous and favourable life. Furthermore, the concepts of measure combined the cosmological order with the mathematical proportion, logical principles of recognition with the methodological arrangements for the truth approximation.